Implementation of Inquiry Learning Based on Creativity and Science Process Skills - Jurubahasa Sinuraya; Motlan; Satria Mihardi; Abd Hakim S (Postgraduate, University of Mataram, 2024)
After inquiry learning research is carried out, it is necessary to investigate problems and find problems based on clear concepts based on observations. Creativity is the ability to create something new. The proposed activities are based on physical phenomena through experiments. Prior knowledge of a problem may detract from an investigation, as it may prefer to retain known evidence rather than devise new alternatives. Creativity is the ability to think to come up with solutions, ideas, ways, products as solutions to existing problems. Innovative is the process of doing something in a new way. The process skills of discovering and developing concepts, theories, legal principles and facts are science process skills (KPS). Based on investigations and problem findings, creative inquiry learning with a process skills approach is used. The method in this research is analysis of indicators of inquiry learning syntax (problem formulation, hypothesis formulation, data collection, hypothesis testing and conclusions), creativity (KE experimental group and KK control group) and science process skills (KE and KK). The concepts developed mutually support inquiry, creativity and process skills. Students' ability to investigate and find problems can be realized.